ABOUT RESERVES OF INCREASE THE STRENGTH AND STABILITY OF JOINTLESS TRACK - Novakovych, M. V.; Hryhorieva, L. O.; Kurylina, I. O. (Science and Transport Progress, 2003)
The new approach to calculation is offered to a track without joints on durability and stability in the article.